Perancangan User Interface Sistem Kredit Aktivitas Mahasiswa STMIK “AMIKBANDUNG” Berbasis Website Menggunakan Metode User Centered Design (UCD) - Rudi Kurniawan; Dika Prananda Putra (Journal of Information Technology, 2022)
In order to achieve graduate quality standards that are not only oriented to hard skills, STMIK "AMIKBANDUNG" stipulates Student Activity Credit regulations. This regulation is a system for declaring recognition of achievements in developing soft kills in the student field. With this system, to achieve graduation, students are required to collect a number of activity credits in accordance with predetermined standards in a timely manner. In its implementation, there are still many credit scores of STMIK "AMIKBANDUNG" students who have not reached the target when they are in the final year. To overcome these problems, one of the solutions offered is to build a website-based Student Activity Credit system. This causes students to have difficulty getting information on the results of their submissions and knowing the activity credits that have been collected. User Interface design using the User Centered Design (UCD) method has resulted in the design of a Student Activity Credit System user interface that is in accordance with the needs of students in applying for activity credit. This is shown based on the results of the evaluation using usability testing, it is known that the average item on the usability variable obtains a total score of > 126 which means there is no problem and a total score of > 102 which means that there is no need for improvement. Keywords— Student Activity Credit, KAM Website User Interface, User Centered Design (UCD) Method, Usability Testing KAM Website.